Prevalence and associated factors of TB and HIV coinfections among adult inmates with presumptive pulmonary TB in a Kenyan prison - Suleiman Athuman Mwatenga; Ali A. Musa; Margaret W. Muturi; Abednego Moki Musyoki (Tropical Medicine and Health, 2024)
Abstract Background Tuberculosis (TB) is more than ten times higher in prisons compared to the general population, and HIV-infected persons are at increased risk of developing active TB and death. In the World Health Organization (WHO) African region, however, where the TB and HIV coinfections are highest, and prisons rarely factored in national disease surveillance, epidemiological data to inform TB control interventions in correctional facilities is limited. In this study, we assessed the prevalence of TB and HIV coinfections, as well as the factors associated with coinfections in our study setting. Methods This was a prospective cross-sectional study among 157 adult (≥ 18 years) prisoners presenting with symptoms of pulmonary TB at Shimo La Tewa Prison, Kenya, between January and June 2023. The study excluded those with a history of anti-TB drugs use or on treatment follow-up and collected demographic and clinical characteristics data using a questionnaire. Sputum samples were collected and processed immediately using Xpert® MTB/RIF assay or stored at 4 °C for three (3) days in case of delay. Results The overall prevalence of TB among inmates with presumptive pulmonary TB was 10.2%, 95% CI 6.37–16.91% (16/157), HIV 19.1%, 95% CI 13.73–25.97% (30/157). All the TB cases were positive for HIV (16/16, 100%), translating to TB/HIV coinfection of 10.2%, 95% CI 6.37–16.91% (16/157), and there was no rifampicin resistance. TB and HIV coinfection cases were found among underweight (100%, 16/16) prisoners. The independent factors associated with TB and HIV coinfections were education level (adjusted OR = 0.17, p = 0.007), smoking history (adjusted OR = 3.01, p = 0.009) and illegal drug use history (adjusted OR = 4.55, p = 0.044). Conclusion We report a high prevalence of pulmonary TB and HIV coinfections among adult inmates with presumptive pulmonary TB in Kenya, with education level, smoking status, and illegal drug use as the independent factors associated with the coinfection. The authority should take measures to protect HIV-positive prisoners from TB, focusing on education, nutrition, smoking, and illegal drug use.